Genetics of resistance to Hessian fly (Mayetiola destructor) [Diptera : Cecidomyiida] biotype L in diploid wheat - Sharma, H.C.; Ohm, H.W.; Patterson, F.L.; Benlhabib, O.; Cambron, S. (Phytoprotection, 1997)
Hessian fly (Mayetiola destructor) is a serious pest of wheat (Triticum spp.) and of the reported biotypes of Hessian fly, biotype L is described as the most virulent. Inheritance of resistance to Hessian fly biotype L was investigated in crosses of a resistant accession of Triticum monococcum, and two susceptible accessions of T. monococcum and one susceptible accession of T. boeoticum, all diploid wheats. F2 and testeross (backeross) families were classified for reaction to Hessian fly in the seedling stage and analysed by Chi-square goodness-of-fit tests for genetic segregation ratios of resistant or segregating families to susceptible families. Resistance was found to be simply inherited, controlled by one or two genes. This is the first report on the inheritance of resistance to Hessian fly in A-genome diploid wheats, and simple genetic control indicates possibility of transfer of this trait to cultivated wheats.